Beating the odds : Eddie Brown's investing and life strategies - Brown, Eddie (Eddie C.), 1940-; Walker, Blair S. (Hoboken, N.J. : John Wiley & Sons, 2011)
"The book is the improbable, inspiring autobiography of financial guru Eddie C. Brown, one of the nation's top stock pickers and money managers. It details how Brown skillfully kept Brown Capital Management afloat through the dot-com bust, 9/11 and the Great Recession. Born to a 13-year-old unwed mother in the rural South, this African-American investment whiz created a Baltimore-based financial firm that accumulated more than $2.5 billion under management. Brown delves into the profound heartbreak and disorientation upon the death of his beloved grandmother - who was his surrogate mother -- and recounts how Brown's moonshine-running Uncle Jake subsequently became the dominant adult figure in Brown's life. His unflinchingly honest, easy-to-read memoir details how intellectual curiosity, abiding self-belief, hard work and divine providence helped Brown earn an electrical engineering degree, become an Army officer, and later a civilian IBM engineer. Readers will learn of the strife that ensued when Brown quit IBM to earn an MBA, leading to investment jobs that prepared him to start his own money management company in 1983"--
Prologue. -- Who Says Talk is Cheap? -- The Big Three to the Rescue. -- The Prince of Apopka. -- Death and a Kidnapping. -- Magnificent, Mysterious Lady B. -- Engineering a New Existence. -- Europe On Five Dollars a Day. -- 'Ed, We're Already Doing Okay!'. -- A Famished Lion in a Butcher Shop. -- The Height of Duplicity and Betrayal? -- A Window on the Top 1 Percent. -- Pulling the Trigger on Investment. -- Swimming with Sharks. -- Aren't You That Financial Guy From TV? -- Walking a Racial Tightrope. -- 'Go For It, Dad!'. -- Everyone's Medical Nightmare. -- My Biggest Business Mistake. -- A Horror Movie Without Sound. -- The Art and Science of Stock Picking. -- 'God, I Owe You One!'. -- Impressive Progress, Baffling Lethargy. -- To Heir Is Human. -- Anyone Care for a Can of New Coke? -- Epilogue. -- About the Authors.
Includes index.
Keywords: Brown, Eddie -- 1940-; Investment advisors -- Florida -- Biography; African American businesspeople -- Florida -- Biography